Fiscal Adjustment in Transition Countries : Evidence From the 1990's - Purfield, Catriona (IMF Working Papers; Working Paper ;, 2003)
In the 1990s, transition countries underwent large adjustments to address fiscal imbalances. This paper examines whether the factors identified in the literature on advanced economies, the size and composition of adjustment, are important in transition economies. It finds that larger consolidations were more successful in addressing fiscal imbalances on a durable basis. Policies focusing on expenditure reductions were more successful than those relying on revenue increases. There is little evidence of expansionary fiscal contractions, but fiscal contractions did not have a significantly negative impact on growth either. Few fiscal stimuli succeeded in boosting growth.